2014
DOI: 10.1152/jn.00534.2014
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine transporter gene susceptibility to methylation is associated with impulsivity in nonhuman primates

Abstract: Impulsivity, the predisposition to act without regard for negative consequences, is a characteristic of several psychiatric disorders and is thought to result in part from genetic variation in the untranslated region of the dopamine transporter (DAT) gene. As the exact link between genetic mutations and impulsivity has not been established, we used oculomotor behavior to characterize rhesus monkeys as impulsive or calm and genetic/epigenetic analysis and positron emission tomography (PET) to correlate phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 55 publications
2
15
0
Order By: Relevance
“…Recently, correlation between impulsivity and eye movements has been shown in humans (Munoz et al, 2003;Cirilli et al, 2011;Hakvoort Schwerdtfeger et al, 2012) and monkeys (Rajala et al, 2012). In particular, Rajala et al (2014) found that the availability of DA transporter in the basal ganglia correlated with the rate of early saccades in the triggered MS task with a long delay (up to 6 s), suggesting that reduced DA might cause impulsive behavior. Considering that striatal DA improves the signal-to-noise ratio in medium spiny neurons (Rolls et al, 1984;Kiyatkin and Rebec, 1996; for review, see Nicola et al, 2000), increased baseline activity following the application of a DA antagonist might render the system more responsive to distracting stimuli.…”
mentioning
confidence: 98%
“…Recently, correlation between impulsivity and eye movements has been shown in humans (Munoz et al, 2003;Cirilli et al, 2011;Hakvoort Schwerdtfeger et al, 2012) and monkeys (Rajala et al, 2012). In particular, Rajala et al (2014) found that the availability of DA transporter in the basal ganglia correlated with the rate of early saccades in the triggered MS task with a long delay (up to 6 s), suggesting that reduced DA might cause impulsive behavior. Considering that striatal DA improves the signal-to-noise ratio in medium spiny neurons (Rolls et al, 1984;Kiyatkin and Rebec, 1996; for review, see Nicola et al, 2000), increased baseline activity following the application of a DA antagonist might render the system more responsive to distracting stimuli.…”
mentioning
confidence: 98%
“…Gene × environment interactions like that reported for the 5HTTLPR variants may be an important aspect of primate behavioral genetics, with broad implications. Other researchers have reported simple genetic associations or gene × environment interactions involving other genes: MAOA (Newman et al, ), TPH2 (Chen et al, ), COMT (Gutleb, Roos, Noll, Ostner, & Schulke, ; Pfluger et al, ), DAT (Rajala et al, ), and MECP2 (Liu et al, ). We may find that early developmental experience can alter the mean phenotype associated with particular genotypes at various loci.…”
Section: Response To Novel Conspecifics and Other Social Challengesmentioning
confidence: 99%
“…However, a growing body of study have suggested that epigenetic modifications can occur in response to a various contextual signals, not only in utero and in early infancy (van Heesbeen et al 2013), but throughout the development (Moore et al, 2013). Regarding methylation status of DAT1 gene, data from animal studies have evidenced that environmental adverse experiences during embryonic phase trigger modifications in DAT level and also found significant association between hypermethylation of the DAT gene and greater availability of DAT (Rajala et al, 2014). Despite the previous premises, a small body of studies have focused on methylation status of DAT promoter in humans, who may mediate effects of environmental risk factors known to contribute to an increased psychopathological risk in children (Schuch et al 2015).…”
Section: Epigenetic: the Role Of Methylation Status Of Dat Promoter Genementioning
confidence: 99%